2018
DOI: 10.1186/s12888-018-1786-8
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory impairment in first-episode schizophrenia: a case-control study, and sex dimorphism in the relationship between olfactory impairment and psychotic symptoms

Abstract: BackgroundA body of studies has focused on the olfactory impairment among people with schizophrenia. The effect of sex on this relationship has attracted the attention of researchers. These issues have not been studied much in Chinese schizophrenia patients.MethodsWe conducted a case-control study of 110 first-episode antipsychotic medicine naïve schizophrenia patients aged 18–35 years and 110 controls, matched by age and sex. Odour threshold, discrimination and identification were assessed by the “Sniffin’ St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
(45 reference statements)
0
14
1
Order By: Relevance
“…There were studies support the right-specific alternation (Nguyen et al, 2011; Turetsky et al, 2003), but others did not find such laterality (Asal et al, 2018; Turetsky et al, 2000, 2018). Sex-associated changes in olfactory deficits have also been frequently discussed (Boesveldt et al, 2017; Chen et al, 2018b; Sorokowski et al, 2019). Possible differences between affective and non-affective psychosis in olfactory deficits are also an important question (Kamath et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were studies support the right-specific alternation (Nguyen et al, 2011; Turetsky et al, 2003), but others did not find such laterality (Asal et al, 2018; Turetsky et al, 2000, 2018). Sex-associated changes in olfactory deficits have also been frequently discussed (Boesveldt et al, 2017; Chen et al, 2018b; Sorokowski et al, 2019). Possible differences between affective and non-affective psychosis in olfactory deficits are also an important question (Kamath et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these deficits are observed in youths at-risk for psychosis (Brewer et al, 2003; Kotlicka-Antczak et al, 2017; Woodberry et al, 2010). Accordingly, olfactory dysfunction is also one of the key deficits in patients with first episode psychosis (FEP) (Chen et al, 2018b; Kamath et al, 2014, 2018, 2019). Furthermore, olfactory deficits appear to predict poor outcomes in patients with schizophrenia (SZ) and can identify patients at high risk of developing unremitting negative symptoms, particularly anhedonia (Good et al, 2010; Lin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory pollution from noise, glare or heat/cold are acknowledged as possible triggers for hallucination. However, people with schizophrenia may not have olfactory sensibilities [24,25]. One participant (#07) referred to her lack of sense of smell when discussing the position of the kitchen exhaust fan, which was not directly above the hot plate.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that NC and SS males differ remarkably in terms of sympathetic sensitivity, and the number of neurons with N-methyl-D-aspartate (NMDA) receptors in the hypothalamic periventricular nucleus is significantly decreased in SS males [ 17 ]. Furthermore, schizophrenia, with which patients sometimes complain of decreased libido and erectile dysfunction, also includes an anosmic symptom [ 4 ]. Thus, the marked differences in the brains of SS males might be caused by factors other than neuroendocrine distortion, which emerge as a particular symptom, such as declined sexual activity and hyposensitive olfaction.…”
Section: Discussionmentioning
confidence: 99%